The influence of reinforcement temperature on stiffness of reinforced concrete beams in fire conditions - Michał Głowacki; Marian Abramowicz; Robert Kowalski (Budownictwo i Architektura, 2013)
This paper describes the analysis of high temperature influence on beams with heated tensile zone. High temperature experiments were preformed under the static load of 50 or 70% of the destructive force ensuring constant value of bending moment in the central part of the heated beam. Beams with 2 reinforcement ratios – 0.44 and 1.13% were examined. In total four series of beams, three in each series (12 elements) were used. This paper analyses the reduction of relative beam cross section stiffness depending on reinforcement temperature. Experimentally obtained stiffness values calculated in two ways (element maximal deflection and deflection measured in three points of analysed element) were compared to calculation results made according to Eurocode. The performed analysis shows that reduction of the stiffness of element based on Eurocode calculations is slightly bigger than the experimentally obtained one.